2004
DOI: 10.1086/381093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features Associated with Bacteremia Due to Heterogeneous Vancomycin‐IntermediateStaphylococcus aureus

Abstract: We assessed all episodes of methicillin-resistant Staphylococcus aureus (MRSA) bacteremia at our hospital during a 12-month period (n=53) and compared those due to heterogeneous vancomycin-intermediate S. aureus (hVISA; n = 5, 9.4%) with those due to vancomycin-susceptible MRSA (n=48). Patients with hVISA bacteremia were more likely to have high bacterial load infections (P=.001), vancomycin treatment failure (persistent fever and bacteremia for >7 days after the start of therapy; P<.001), and initially low se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
289
7
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(308 citation statements)
references
References 17 publications
11
289
7
1
Order By: Relevance
“…Accumulating data demonstrate that vancomycin is less effective when the MIC of S aureus is higher than 1 g/mL than when the MIC is 1 g/mL or less. [8][9][10][11] The lack of relevant data in these trials did not allow us to study whether the VANCOMYCIN FOR GRAM-POSITIVE INFECTIONS: A META-ANALYSIS higher effectiveness of comparator antibiotics could be due to higher MICs. Several trials reported (without presenting quantitative data) that development of resistance was not observed during the trial period, thus rejecting the hypothesis that resistance may have been the reason for vancomycin's lower effectiveness.…”
Section: Vancomycin For Gram-positive Infections: a Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating data demonstrate that vancomycin is less effective when the MIC of S aureus is higher than 1 g/mL than when the MIC is 1 g/mL or less. [8][9][10][11] The lack of relevant data in these trials did not allow us to study whether the VANCOMYCIN FOR GRAM-POSITIVE INFECTIONS: A META-ANALYSIS higher effectiveness of comparator antibiotics could be due to higher MICs. Several trials reported (without presenting quantitative data) that development of resistance was not observed during the trial period, thus rejecting the hypothesis that resistance may have been the reason for vancomycin's lower effectiveness.…”
Section: Vancomycin For Gram-positive Infections: a Meta-analysismentioning
confidence: 99%
“…In addition, its use has increased throughout the years, especially in some settings, 1 mainly because of the emergence of ␤-lactam-resistant staphylococci and enterococci. Although vancomycin has proved effective for the treatment of patients with gram-positive infections, several studies have emphasized some important disadvantages, including nephrotoxicity and other adverse reactions, 2-4 the need for continuous monitoring of its trough serum levels, 5 relatively poor pharmacokinetic properties (especially in the lungs), 6,7 data pointing toward reduced effectiveness when the minimal inhibitory concentration (MIC) of Staphylococcus aureus was higher than 1 g/mL, [8][9][10][11] and vancomycin resistance or increasing MICs. 12 However, vancomycin continues to be the treatment of choice for serious resistant gram-positive infections (including bacteremia, pneumonia, endocarditis, and complicated skin and soft tissue infections [SSTIs]) in the published guidelines of medical societies.…”
mentioning
confidence: 99%
“…However, recent literature has created an increased awareness of Staphylococcus aureus isolates that are heterogeneously resistant to vancomycin otherwise known as hVISA. 16,17 The development of hVISA is associated with low vancomycin concentrations making the appropriate empiric dosing of vancomycin critical if clinicians want to have vancomycin available as an option for the treatment of MRSA in the future.…”
Section: Introductionmentioning
confidence: 99%
“…7 Low vancomycin trough levels have been implicated in the emergence of hVISA, and several studies have demonstrated a higher rate of vancomycin treatment failure, longer duration of fever, and prolonged hospitalization with hVISA and strains with elevated MIC compared to vancomycin-susceptible MRSA. [8][9][10][11][12] Until recently, vancomycin was frequently dosed to target trough levels <10 mg/L. The above concerns, combined with pharmacodynamic data suggesting that maintaining a ratio of vancomycin area under the curve to minimum inhibitory concentration (AUC/ MIC) !400 may be associated with improved clinical outcome, 13 have prompted an expert consensus to recommend targeting higher vancomycin trough levels (typically 15-20 mg/L) for invasive MRSA infections and general avoidance of trough levels <10 mg/L.…”
mentioning
confidence: 99%